Economic Disruption and Language Shift – Some Ethnographic Data from Ireland After the 2008 Crash - Ceallaigh, Ben Ó (Studia Celtica Posnaniensia, 2021)
This paper discusses some of the ways in which the “Great Recession” which followed the 2008 economic crash affected the vitality of Irish-speaking (“Gaeltacht”) areas. In addition to a brief discussion of the nature of neoliberalism – the cause of the 2008 crash – and some of the ways in which this ideology stands in contradiction to the requirements of language revitalisation, examples are given to illustrate the way in which the recession affected state language policy. Various microlevel consequences of these macro-level economic and policy developments are then discussed by reference to ethnographic data gathered in the Gaeltacht. Issues such as deindustrialisation, unemployment and the problematic nature of tourism in minoritised language communities are discussed, as is language use amongst young people and the way in which technology can contribute to language shift. The paper concludes with a discussion of the potential for anti-systemic movements and policy proposals such as the “Green New Deal” to create, coincidentally, a macroeconomic regime that would be more favourable to linguistic minorities than that of neoliberalism.